Real-time deterministic power flow control through dispatch of distributed energy resources - Fazeli, Amir; Sumner, M.; Johnson, Christopher Mark; Christopher, Edward (IET, 2015)
Integration of intermittent renewable resources and mass electrification of heat and transport into the existing electricity network, with limited network asset reinforcement requires incorporation of intelligence in form of active management of flexible resources within different sections of the distribution network. A hierarchical multi-level control framework is proposed for this purpose which incorporates the appropriate optimisation and control strategies at different levels. In particular a novel deterministic control algorithm for controlling power flows at the community cell level has been developed and presented in this paper. This algorithm incorporates robustness to communication and device failure and is easily expandable to an arbitrary number of devices. The simulation results presented in this paper show that the effectiveness of the proposed control technique depends on distributed energy resources flexibility and storage capacity.